2020
DOI: 10.1155/2020/6839103
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Bronchoalveolar Lavage Fluid Metagenomic Next-Generation Sequencing in Pneumonia

Abstract: Background. Metagenomic next-generation sequencing (mNGS) has made a revolution in the mode of pathogen identification. We decided to explore the diagnostic value of blood and bronchoalveolar lavage fluid (BALF) as mNGS samples in pneumonia. Methods. We retrospectively reviewed 467 mNGS results and assessed the diagnostic performance of paired blood and BALF mNGS in 39 patients with pneumonia. Results. For bacteria and fungi, 16 patients had culture-confirmed pathogen diagnosis, while 13 patients were culture-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 32 publications
6
62
2
Order By: Relevance
“…Body Fluid Sample: Sample Processing and DNA Extraction A body fluid sample (1.5-3 mL of BALF, pleural effusion, or sputum) was collected from each patient according to standard procedures [5]. A 1.5-mL microcentrifuge tube containing 0.6 mL sample, enzyme, and 1 g of 0.5-mm glass beads was agitated by a vortex mixer, and a 0.3-mL sample was separated into a 1.5-mL microcentrifuge tube and DNA was extracted using the TIANamp Micro DNA Kit (DP316, Tiangen Biotech) following the manufacturer's operational manual.…”
Section: Metagenomic Next-generation Sequencing and Analysismentioning
confidence: 99%
“…Body Fluid Sample: Sample Processing and DNA Extraction A body fluid sample (1.5-3 mL of BALF, pleural effusion, or sputum) was collected from each patient according to standard procedures [5]. A 1.5-mL microcentrifuge tube containing 0.6 mL sample, enzyme, and 1 g of 0.5-mm glass beads was agitated by a vortex mixer, and a 0.3-mL sample was separated into a 1.5-mL microcentrifuge tube and DNA was extracted using the TIANamp Micro DNA Kit (DP316, Tiangen Biotech) following the manufacturer's operational manual.…”
Section: Metagenomic Next-generation Sequencing and Analysismentioning
confidence: 99%
“…For SCAP patients, the pathogen positivity rate was 90.3% for mNGS versus 39.5% for conventional methods ( Wu et al., 2020 ). The feasibility of mNGS for bronchoalveolar lavage fluid (BALF), blood, sputum, transbronchial lung biopsy (TBLB) and even lung biopsy tissues ( Li et al., 2018 ; Liu et al., 2019 ; Chen et al., 2020 ; Li et al., 2020 ; Wu et al., 2020 ) in patients with respiratory infections has been demonstrated in many literatures. However, the high cost affects the wide application of mNGS in CAP patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huang et al used mNGS to detect microbes related to human diseases in 94.49% of samples from patients with pulmonary infections who had received negative results from traditional pathogen detection methods, indicating that the accuracy and sensitivity of mNGS are higher than those of standard pathogen detection techniques [ 28 ]. Similarly, Wang et al found that mNGS was more sensitive than traditional methods in mixed pulmonary infections [ 13 ] whereas Chen et al found that the results obtained using mNGS in BALF of patients with severe disease were highly consistent with those of culture [ 29 ].…”
Section: Discussionmentioning
confidence: 99%